TRANSPORT OF URANIUM, THORIUM, AND LEAD IN METAMICT ZIRCON UNDER LOW-TEMPERATURE HYDROTHERMAL CONDITIONS - Geisler T.; Kurtz R.; Pidgeon R.T.; Van Bronswijk W. (My University, 2002)
Understanding the stability of radiation-damaged zircon under low-temperature hydrothermal conditions is crucial to the application of zircon for U–Pb geochronology and as a host phase for the disposal of plutonium waste. We report the results of an investigation of the stability of partially metamict zircon by leaching experiments at 175 °C with a 2 M AlCl3 and a 1 M HCl–CaCl2 solution as hydrothermal fluids for 1340 h. Cathodoluminescence (CL) and backscattered electron (BSE) images show that the zircon grains have developed a reaction rim several micrometers thick or deeply penetrating reticulated alteration zones with sharp boundaries to unaltered metamict zircon. These zones have experienced severe loss of Si, U, Th, and Pb, and gain of Al or Ca, and a water species as revealed by electron microprobe, sensitive high-resolution ion microprobe (SHRIMP) analyses, and infrared spectroscopy. Micro-Raman and infrared measurements on the altered areas show that disordered crystalline remnants of the partially metamict zircon structure were partially recovered, whereas recrystallization of the embedding amorphous phase was not observed. No detectable structural or chemical changes were detected inside the unaltered areas. Intensive fracturing, which was most intense in the HCl–CaCl2 experiment, occurred inside the altered areas due to the volume reduction associated with the recovery of the disordered crystalline material and probably with the leaching reactions. We explain the formation of deep penetrating alteration zones by a percolation-type diffusion model, which is based on the assumption that percolating interfaces or areas of low atomic density between crystalline and amorphous regions as well as between amorphous domains exist along which fast chemical transport is possible. The idea of the existence of fast diffusion interfaces is supported by the sharp chemical gradients at the margin to unreacted zircon. The model was used to estimate for the first time diffusion coefficients for U, Th, and Pb diffusion in amorphous zircon at 175 °C by assuming that volume diffusion inside the amorphous domains is the loss rate-limiting process. These estimates show that volume diffusion in metamict zircon can cause significant loss of U, Th, and especially loss of radiogenic Pb over geological time scales, even at temperatures as low as 175 °C. Our results show that recent Pb loss discordias can be generated (1) by predominate Pb loss from metamict zircon through volume diffusion at low temperatures where thermal healing of the structure is insignificant, and (2) by leaching of Pb (and U and Th) from metamict zircon through an external fluid.